2020
DOI: 10.1093/annweh/wxaa064
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Absorption of PAHs in Wildland Firefighters: A Field Study with Pilot Interventions

Abstract: Objectives There is limited knowledge of exposure to polycyclic aromatic hydrocarbons (PAHs) in wildland firefighters, or of the effectiveness of interventions to reduce this. This study of wildland firefighters assessed whether PAHs were present and considered respiratory protection and enhanced skin hygiene as possible interventions. Methods 1-Hydroxypyrene (1-HP) was measured in urine samples collected pre-shift, post-shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 16 publications
1
38
1
Order By: Relevance
“…Five research articles [ 20 – 24 ] and no grey literature reported on studied mitigation strategies. One grey literature report provided information about critical incident management [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five research articles [ 20 – 24 ] and no grey literature reported on studied mitigation strategies. One grey literature report provided information about critical incident management [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…• Mean increase in 1-hydroxypyrene in urine samples collected post shift in 76% of participants [ 20 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown evidence here of the very limited respiratory protection achieved by RPE, particularly in the early days of the fire. Elsewhere we have shown the importance of skin hygiene to reduce absorption of polycyclic aromatic hydrocarbons both in urban and industrial firefighters in the Fort McMurray fire ( 7 ) and in wildland firefighters ( 23 ). The importance of administrative controls, in reducing exposures by deploying firefighters in rapidly rotating shifts, is demonstrated by the mean exposures during the first rotation shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%